Znaczenie kosztów jakości w systemie zarządzania jakością - Balon, Urszula; Boratyńska-Sala, Anna (Significance of Quality Costs in the Quality Management System, 2007)
The paper presents an idea and review of quality cost models. Through monitoring of quality costs one can analyse trends, determine causes of poor quality costs and identify areas generating high quality costs in a company. Properly performed monitoring of quality costs is an effective tool of company management of measurable effects, including financial outcome of a company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 13-24